Sequenciamento dos genes Mrjp3, Mrjp5, Mrjp8 de abelhas Apis mellifera africanizadas - Pozza, Arielen Patrícia Balista Casagrande (2011)
Sequencing ofthe MRJP3, MRJP5 and MRJP8 genes from Africanized Apis mel4fera In the present study was performed the aliele sequencing ofthe Mrjp3, MrJp5 and mJp8 loci from Africanized A. mellfera selected to produce royal jelly. The genomic DNA was extracted from 20 nurse bees obtained from 7 hives producing royal jeily of the UEM?s genetic bees improvement for royaljeily production, totaling 140 samples. The Mrjp3, Mrjp5 and MrJp8 microsateilite loci were amplified using specific primers. The three loci produced a total of 16 alieles, of which 10 homozygous alieles were sequenced. The mrp3 locus had the C, D, E, F, G sequenced, the Mrj5 had the D, E, F alieles sequenced and the MrJp8 had the C and D alieles sequenced. Ali the sequenced and aiigned alleles showed high similarity with the ones previousiy described. The Mrjp3 alieles that show association with the royal jelly production are being kept in the analyzed matrixes, as the locus has great potential to be considered a molecular marker of the royal jelly production in Africanized A. mellfera. The C, D and E alleles from MrJp5 are also being selected, although their association with the production of royal jelly needs to be analyzed. The MRJP8 has no direct role in the royal jelly production its expression is being detected in the poison glandule and so, its alleles are not being selected. The maintenance of the matrixes carrying the selected alleles of MRJP3 and MRJP5 must be performed using an instrumental insemination program along with the analysis of the royal jelly production in the descending queens and of the selected molecular markers.